2020
DOI: 10.31557/apjcp.2020.21.11.3325
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Vitamin A in Reducing β-hCG Levels in Low-Risk Gestational Trophoblastic Neoplasia Patients

Abstract: Objective: Low-risk gestational trophoblastic neoplasia (GTN) is generally treated with single agent chemotherapy and methotrexate (MTX) as a first-line therapy. Vitamin A helps to increase trophoblast cell regression, as well as to decrease β-hCG levels. Vitamin A also increases the effectiveness of MTX by inducing more malignant cell death than MTX alone. Therefore, the aim of the current study was to analyze the changes in β-hCG levels in low-risk GTN patients following vitamin A administration. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The estimated incidence of hydatidiform mole and GTN in Cambodia was lower than that in neighboring countries. The incidence of hydatidiform mole (per 1000 pregnancies or 1000 deliveries) was reported as 1.9 in Vietnam, 15 1.70 in Thailand, 21 1.8 in Thai‐Myanmar border, 22 2.8 in Malaysia, 23 2.3 in Indonesia, 24 and 2.4 in the Philippines 25 . The incidence of GTN (per 100 000 pregnancies or 100 000 deliveries) was 100 in Thailand 26 and 121 in Indonesia, 24 although fewer studies on GTN were reported compared to studies on hydatidiform mole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated incidence of hydatidiform mole and GTN in Cambodia was lower than that in neighboring countries. The incidence of hydatidiform mole (per 1000 pregnancies or 1000 deliveries) was reported as 1.9 in Vietnam, 15 1.70 in Thailand, 21 1.8 in Thai‐Myanmar border, 22 2.8 in Malaysia, 23 2.3 in Indonesia, 24 and 2.4 in the Philippines 25 . The incidence of GTN (per 100 000 pregnancies or 100 000 deliveries) was 100 in Thailand 26 and 121 in Indonesia, 24 although fewer studies on GTN were reported compared to studies on hydatidiform mole.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hydatidiform mole (per 1000 pregnancies or 1000 deliveries) was reported as 1.9 in Vietnam, 15 1.70 in Thailand, 21 1.8 in Thai‐Myanmar border, 22 2.8 in Malaysia, 23 2.3 in Indonesia, 24 and 2.4 in the Philippines 25 . The incidence of GTN (per 100 000 pregnancies or 100 000 deliveries) was 100 in Thailand 26 and 121 in Indonesia, 24 although fewer studies on GTN were reported compared to studies on hydatidiform mole. The incidence of hydatidiform mole and GTN might be lower than estimated according to the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical trial demonstrated the effect of oral vitamin A (6,000 IU/day) in patients (n = 32) with low-risk gestational trophoblastic neoplasia who receive methotrexate chemotherapy ( 141 ). The intervention group exhibited a reduction of chemoresistance as well as a downregulation of the tumor marker β-hCG level ( 141 ).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Another clinical trial demonstrated the effect of oral vitamin A (6,000 IU/day) in patients (n = 32) with low-risk gestational trophoblastic neoplasia who receive methotrexate chemotherapy ( 141 ). The intervention group exhibited a reduction of chemoresistance as well as a downregulation of the tumor marker β-hCG level ( 141 ). It was reported in a randomized double-blind study that using vitamin A supplementation (8,000 IU/8 h) with neoadjuvant chemotherapy (64 weeks) in 15 patients (total sample size is 30) has significantly improved the therapeutic response in the treatment of an advanced cervical carcinoma ( 142 ).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Hydatidiform mole occurs in 1:51 to 1:141 pregnancies in Indonesia, and 1:28 to 1:105 pregnancies in West Java [3]. In Bandung, the incidence is 1:427 pregnancies, while GTN occurs in 1:822 pregnancies [4]. After evacuation, a complete mole exhibits a 15-20% likelihood of progressing to malignancy, while a partial hydatidiform A R T I C L E I N F O mole has a less than 5% risk of developing into GTN [5].…”
Section: Introductionmentioning
confidence: 99%